2000
DOI: 10.1042/bj3510817
|View full text |Cite
|
Sign up to set email alerts
|

N-acyl-dopamines: novel synthetic CB1 cannabinoid-receptor ligands and inhibitors of anandamide inactivation with cannabimimetic activity in vitro and in vivo

Abstract: We reported previously that synthetic amides of polyunsaturated fatty acids with bioactive amines can result in substances that interact with proteins of the endogenous cannabinoid system (ECS). Here we synthesized a series of N-acyl-dopamines (NADAs) and studied their effects on the anandamide membrane transporter, the anandamide amidohydrolase (fatty acid amide hydrolase, FAAH) and the two cannabinoid receptor subtypes, CB1 and CB2. NADAs competitively inhibited FAAH from N18TG2 cells (IC50 = 19–100µM), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
197
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(208 citation statements)
references
References 48 publications
7
197
1
1
Order By: Relevance
“…Remarkably, exogenously applied NADA could facilitate glutamate release via TRPV1 even in the absence of the CB1-R antagonist, when tested at low doses (1 mM). This is in agreement with a reported higher effect of NADA at TRPV1 than at CB1-R (Bisogno et al, 2000;Huang et al, 2002b). It is worth to note that NADA, when applied at a high dose (10 mM) and in the absence of either CB1-R or TRPV1 antagonists, did not significantly modify glutamate transmission to the DA neurons.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Remarkably, exogenously applied NADA could facilitate glutamate release via TRPV1 even in the absence of the CB1-R antagonist, when tested at low doses (1 mM). This is in agreement with a reported higher effect of NADA at TRPV1 than at CB1-R (Bisogno et al, 2000;Huang et al, 2002b). It is worth to note that NADA, when applied at a high dose (10 mM) and in the absence of either CB1-R or TRPV1 antagonists, did not significantly modify glutamate transmission to the DA neurons.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown a functional role of TRPV1 in the ventral midbrain (Marinelli et al, 2003(Marinelli et al, , 2005 and other studies have demonstrated a presynaptic modulation of neurotransmission by CB1 in the same area Melis et al, 2004). Compared with AEA, NADA is more potent at TRPV1 and less potent but more efficacious at CB1-R (Bisogno et al, 2000;Bezuglov et al, 2001;Huang et al, 2002b).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Other endocannabinoids have since been identified including 2-arachidonoylglycerol, noladin ether and N-arachidonoyl dopamine [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Other recently described endogenous cannabinoids are 2-arachidonyl glyceryl ether (noladin ether) [72] , O-arachidonoyl-ethanolamine (virodhamine) [73] and N-arachidonoylethanolamine [74,75] . [76] and AM251 (CB1 receptorselective antagonists), as well as SR144528 [77] and AM630 (CB2 receptor-selective antagonists).…”
Section: Cannabinoidsmentioning
confidence: 99%